'From the time he took on the form of a servant': The Christ's Pilgrimage of Faith. (27th February 2013) - Allen, Michael
Abstract Addressing the pistis christou debate in New Testament studies, this article argues that in the eternal life of the perfect God, the divine Son pleases the Father in the Spirit and, therefore, the divine Son trusts the Father by the Spirit's power during his earthly pilgrimage. It roots soteriology in Christology and shows that the christological account flows forth from the eternal relations of the Trinity. The article concludes by noting implications for dogmatics and exegesis.